Ατομιστικές προσομοιώσεις Μοριακής Δυναμικής νανοσύνθετων υλικών νανοσωλήνας άνθρακα - πολυμερικής μήτρας. - Μπάρδας, Χρήστος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Εφαρμοσμένων Μαθηματικών και Φυσικών Επιστημών, 2017)
Nanocomposite systems which contain carbon nanotubes embedded into polymer matrices constitute a very prominent category of materials for multiple novel applications. One of the most appealing attributes of such materials is the dependency of their properties on the geometrical and physiochemical characteristics of the nanotubes. A key issue that directly affects the properties and the performance of these materials is associated with the inherent tendency of pristine carbon nanotubes to form agglomerates, resulting in poor dispersion in the matrix material. A promising solution to the issue of aggregation relies in the surface modification of nanotubes through chemical or/and physical functionalization utilizing molecules of variable chemical composition, length and geometry. In addition, the functionalization mechanism can also be considered as a way of varying the cohesion forces between the nanotube and the host matrix material. The present thesis focuses on carbon nanotubes, either in their pristine or in substituted forms, using polar carboxylic and hydroxyl groups inside polar acrylic matrices. The scope of our studies is to determine the effect of surface substitution on the properties of the nanocomposite material through Molecular Dynamics Simulations. Initial configurations are generated via the bond-by-bond growth of polymeric macromolecules in the presence of a carbon nanotube of a given surface substitution. Structural, mechanical and dynamical properties are calculated at thermodynamic equilibrium under controlled temperature and pressure for various physicochemical characteristics regarding the carbon nanotube.